Travelers’ Expectations When Booking Hotels Through Online Travel Agents - Jedin, Mohd Haniff; Annathurai, Kohila Ranjini; Mavondo, Felix (UUM Press, 2022)
Travellers constantly require personalized travel arrangements. They look for specific arrangements depending on whether the trip is for leisure or business. However, some travellers prefer multiple events in their travel schedules, including visiting prime locations or historical places. Hence, online travel agents (OTAs) are the most convenient alternative platforms to meet the specific needs of travellers. This study utilizes survey method to examine factors influencing travellers when booking hotels through OTAs. This study collected 398 questionnaires at Penang International Airport, Malaysia. Results indicate five factors, i.e. room facilities and amenities, customer recognition through star rating, price factor, promotion factor, and other hotel facilities, that significantly influence travellers’ expectations in booking hotels through OTAs.